School Refusal Behavior and Aggression in Spanish Adolescents - Gonzálvez, Carolina; Martín, Miriam; Vicent, María; Sanmartín, Ricardo (Frontiers in Psychology, 2021)
In order to reduce school attendance problems and aggressive behavior, it is essential to determine the relationship between both variables. The aim of this study was twofold: (1) to examine the mean differences in scores on aggression, based on school refusal behavior, and (2) to analyze the predictive capacity of high scores on aggression, based on school refusal behavior factors. The sample consisted of 1,455 Spanish secondary school students, aged 13 to 17 (M= 14.85; SD= 1.56). The School Refusal Assessment Scale-Revised (I. Avoidance of Negative Affectivity, II. Escape from Aversive Social and/or Evaluative Situations, III. Pursuit of Attention from Significant Others and IV. Pursuit of Tangible Reinforcement Outside of School) and the Aggression Questionnaire (I. Physical Aggression, II. Verbal Aggression, III. Anger, and IV. Hostility) were used. Results indicated that students having high levels of Physical Aggression, Verbal Aggression, Anger and Hostility received significantly higher scores on school refusal behavior. In most cases, school refusal behavior was found to be a positive and statistically significant predictor of aggression. Students that base their school refusal on the pursuit of tangible reinforcements outside of school earned higher scores, and other functional conditions underlying school refusal behavior were found to be associated with aggression issues. The role of aggression as a risk factor for school refusal behavior is discussed.